2023
DOI: 10.1002/pro.4785
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐perspectives and challenges in identifying B‐cell epitopes

Nishant Kumar,
Nisha Bajiya,
Sumeet Patiyal
et al.

Abstract: The identification of B‐cell epitopes in antigens is a crucial step in developing recombinant vaccines or immunotherapies for various diseases. Over the past four decades, numerous in silico methods have been developed for predicting B‐cell epitopes. However, existing reviews have only covered specific aspects, such as the progress in predicting conformational or linear B‐cell epitopes. Therefore, in this paper, we have undertaken a systematic approach to provide a comprehensive review covering all aspects ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 146 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…The identification of epitopes is important in the development of highly specific and harmless vaccines, and therapeutic and diagnostic antibodies [17,18], since epitopes, namely, allow the immune system to recognize and respond to specific pathogens [19]. Therefore, it is especially important to determine the epitope of an antibody capable of neutralizing one of the significant pathogenic factors of B. cereus in order to design a mimetic, based on which a protection against the action of HlyII of various B. cereus strains can be created.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of epitopes is important in the development of highly specific and harmless vaccines, and therapeutic and diagnostic antibodies [17,18], since epitopes, namely, allow the immune system to recognize and respond to specific pathogens [19]. Therefore, it is especially important to determine the epitope of an antibody capable of neutralizing one of the significant pathogenic factors of B. cereus in order to design a mimetic, based on which a protection against the action of HlyII of various B. cereus strains can be created.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the silico programme was proposed to predict the antigenic epitope for both linear and conformational epitopes. However, the accurate identification of epitopes remains the major challenge for immunoinformaticians (Sun et al ., 2019; Kumar et al ., 2023). Recently, several prediction epitopes methods have been developed, and many studies reported several sites to predict linear epitopes such as BcePred, BepiPred, ABCpred, COBEpro, SVMTriP, LBtope, Emini and LBEEP (Isea, 2017; Manavalan et al ., 2018).…”
Section: In Silico Prediction Of T‐cell Epitopes On Proteinsmentioning
confidence: 99%
“…However, the distinction between CD and NCGS depends on patients' symptoms, according to the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (Tonutti & Bizzaro, 2014; Leonard et al ., 2017). The gluten disorder related to the immune system is producing antibodies against short sequencing of amino acids called epitope (Sanchez‐Trincado et al ., 2017; Kumar et al ., 2023). Many epitopes related to gluten disorder have been identified and listed in various review papers (Panda et al ., 2017; Panda & Garber, 2019a, 2019b), which are later used to follow gluten reduction as a result of treating gluten by food processing techniques.…”
Section: Introductionmentioning
confidence: 99%